Bio-inspired nanocatalysts for the oxygen reduction reaction - Grumelli, Doris Elda (2013)
Electrochemical conversions at fuel cell electrodes are complex processes. In particular, the oxygen reduction reaction has substantial overpotential limiting the electrical power output efficiency. Effective and inexpensive catalytic interfaces are therefore essential for increased performance. Taking inspiration from enzymes, earth-abundant metal centres embedded in organic environments present remarkable catalytic active sites. Here we show that these enzyme-inspired centres can be effectively mimicked in two-dimensional metal-organic coordination networks self-assembled on electrode surfaces. Networks consisting of trimesic acid and bis-pyridyl-bispyrimidine coordinating to single iron and manganese atoms on Au(111) effectively catalyse the reduction and reveal distinctive catalytic activity in alkaline media. These results demonstrate the potential of surface-engineered metal-organic networks for electrocatalytic conversions. Specifically designed coordination complexes at surfaces inspired by enzyme cofactors represent a new class of nanocatalysts with promising applications in electrocatalysis.